Beyond the Pandemic: Art-making lessons for SOTL in an unequal South African context - Kim Berman (University of Johannesburg, 2022)
This article aims to present an arts-based campaign as a strategy to glimpse into 'the fault lines of inequality of access' through the voices of art students and considers hope and imagination as strategies to engage with and move through the despair and trauma emerging out of the COVID-19 pandemic period. The Lockdown Collection (TLC), established at the start of the first hard lockdown in March 2020, is considered, a case study for the Scholarship of Teaching and Learning in the South (SOTL). It reveals greater understanding of ways that visual research pedagogies can develop collective strategies for the individual and community to flourish in the face of the pandemic. Such strategies include the capacities to listen to student voices and raise funds for vulnerable artists. Artists find resilience in their ability to make a difference through their own agency to remake and transform internal and external realities through their artwork and imagine different possibilities. The contention is that economic agency is and must be part of the strategy.